FUNGSI KOGNITIF REMAJA DENGAN INTERNET GAMING DISORDER PADA SISWA SMP DI YOGYAKARTA - GITA DIAH PRASASTI (JURNAL ILMIAH KOHESI, 2022)
The prevalence of Internet Gaming Disorder (IGD) in various countries is increasing rapidly alongside the advancement of technology, ease of internet access and expansion of internet coverage. People with IGD may show symptoms of decreased cognitive function and adolescents are a vulnerable age group due to the lack of control mechanisms. The subjects of this cross-sectional study were students at junior high schools in the Special Region of Yogyakarta Province. The instruments used in this study were the Indonesian version of the Game Addiction Scale-7 questionnaire (GAS-7 Ina) to identify IGD, as well as the Indonesian version of the Modified Mini Mental State Examination for children and adolescents (MMMSEC-Ina) to assess cognitive function. Analysis was later performed to determine the relationship between IGD and cognitive function. The application of behavioral cognitive therapy to overcome marital conflicts for dual-earners is implemented through a comprehensive assessment and implementation techniques. Termination can be done if communication between spouses is more. We obtained data from 120 students that consist of 60 IGD subjects and 60 non IGD subjects with a mean age of 14 years old. Students with IGD had lower total cognitive function scores (p=0.029) than non- IGD students, especially in the domains of calculation/attention (p=0.000) and recalling (p=0.000). Multivariate analysis showed that subjects with IGD tended to have a cognitive function score of 1.34 point lower than the non- IGD subjects. The presence of IGD is negatively associated with cognitive function. Junior high school students with IGD had lower cognitive function scores than non- IGD students, especially in the domains of calculation/attention and recall memory